From Structural to Functional Positions: An Analysis of Human Resource Reform at Indonesia’s Public Broadcasting Institution - Mursalim, Ernawati; Hamka, Hamka; Giyanto , Bambang (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study examines the transition from structural to functional positions at Indonesia’s Public Broadcasting Institution, Radio Republik Indonesia (RRI), through the lens of Weberian bureaucracy. Using a qualitative approach, data were collected through observations, in-depth interviews, and document analysis, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that the transition represents a strategic organizational reform aimed at enhancing professionalism, efficiency, and adaptability in public broadcasting. The implementation reflects key Weberian principles, including division of labor, hierarchical authority, formal rules, impersonality, and career systems, which support competency-based career development and performance accountability. However, several challenges persist, such as task mismatches, incomplete internal regulations, employee resistance, and limited career pathways. Notably, while the division of labor and hierarchical authority function both as enabling and constraining factors, formal rules, impersonality, and career systems predominantly support the reform process. The study concludes that the success of this transition depends on strengthening regulatory frameworks, enhancing human resource capacity, establishing clear competency standards, and ensuring continuous leadership communication and organizational socialization.